공적개발원조 배분정책과 실적: 선진국과 한국의 비교 - 이계우 (12230, 2011)
Ever since the UN Summit agreed on the MDGs in 2000, OECD/DAC member countries have taken poverty reduction as the main goal of their aid. To achieve this goal, all donors and recipient countries agreed on the Paris Declaration on Aid Effectiveness in 200